Changes in awareness of cancer risk factors among adult New Zealanders (CAANZ): 2001 to 2015 - Richards, R; McNoe, B; Iosua, E; Reeder, A I; Egan, R; Marsh, L; Robertson, L; Maclennan, B; Dawson, A; Quigg, R; Petersen, A-C (Health education research, 2017)
Behaviour change, specifically that which decreases cancer risk, is an essential element of cancer control. Little information is available about how awareness of risk factors may be changing over time. This study describes the awareness of cancer risk behaviours among adult New Zealanders in two cross-sectional studies conducted in 2001 and 2014/5.Telephone interviews were conducted in 2001 (n = 436) and 2014/5 (n = 1064). Participants were asked to recall things they can do to reduce their risk of cancer. They were then presented with a list of potential risk behaviours and asked if these could increase or decrease cancer risk.Most New Zealand adults could identify at least one action they could take to reduce their risk of cancer. However, when asked to provide specific examples, less than a third (in the 2014/5 sample) recalled key cancer risk reduction behaviours such as adequate sun protection, physical activity, healthy weight, limiting alcohol and a diet high in fruit. There had been some promising changes since the 2001 survey, however, with significant increases in awareness that adequate sun protection, avoiding sunbeds/solaria, healthy weight, limiting red meat and alcohol, and diets high in fruit and vegetables decrease the risk of developing cancer.